Perlindungan Hukum Terhadap Justice Collaborator Ditinjau Dari UU 31/2014 Dan Hukum Islam - Alifia Nur Basanti; Tajul Arifin (Jurnal Hukum dan Sosial Politik, 2023)
A justice collaborator are suspect, defendants or convicts but work together with law enforcement officials to provide information in uncovering criminal acts that have occurred. The aim of the research is to analyze the legal protection of justice collaborators in terms of Law 31/2014. This study uses normative legal research methods with qualitative data. The results of the study show that (1) Legal protection for justice collaborators in terms of Law Number 31 of 2014 explained in article 5 that law enforcement officials have the obligation to provide protection and assistance to justice collaborator from legal entities so that they feel safe from threats which will come. (2) Legal protection for justice collaborators in terms of five basic principles or commonly called Maqashid Asy-Syariah which can be concluded that Islam highly upholds the protection of human rights, which in this case is legal protection for justice collaborators who have important services in helping officials Law enforcers uncover a crime.